Types of Separation in the Light of the Noble Qur’an: A Doctrinal Study - Jamil Ali Rasul; Mohamad Fakhradeen Mohamad (QALAAI ZANIST JOURNAL, 2022)
This research, entitled (Types of Separation in the Light of the Noble Qur’an - a Doctrinal Study-) consists of an introduction, two chapters and a conclusion. As for the introduction, the researcher dealt with the importance of unity and meeting among believers in Islam, Islam urges unify, unity and harmony, and warns against Dissonance and disagreement, and he touched upon the fact that the Islamic nation has been afflicted with this scourge and great evil, ancient and modern, which is the disease of division and disagreement, and not agreeing on one thing, and the abundance of polemics and quarrels even over simple matters, or disputed issues of jurisprudence. And in the first chapter, which consists of two demands, the research touched on two types of separation, namely: the rejection of Islam and exit from it, and the separation of the infidels among themselves, in the first topic, the research dealt with the talk about abandoning Islam and leaving it, and it is one of the things that God Almighty has forbidden human beings to follow, adhere to and enter into it. And in the second topic, the research touched on the second type of this separation, which is the separation of the infidels among themselves. As for the second Chapter, the research dealt with the issue of disunity due to belief in some Sharia and denial of others, and its effects in reality, which consists of two topics. This topic has shed light on another type of division that occurred among Muslims themselves, and this emerged in general as it affected the belief of Muslims, their unity and their entity. In the first topic, the research discusses the division of Muslims due to belief in some of the Sharia and denial of others, as for the second topic, it touched upon the effects of disunity due to belief in some Sharia, in the conclusion, the research records the results it reached.